2018
DOI: 10.1021/acs.est.7b04384
|View full text |Cite
|
Sign up to set email alerts
|

Chaoborus spp. Transport CH4 from the Sediments to the Surface Waters of a Eutrophic Reservoir, But Their Contribution to Water Column CH4 Concentrations and Diffusive Efflux Is Minor

Abstract: Chaoborus spp. (midge larvae) live in the anoxic sediments and hypolimnia of freshwater lakes and reservoirs during the day and migrate to the surface waters at night to feed on plankton. It has recently been proposed that Chaoborus take up methane (CH) from the sediments in their tracheal gas sacs, use this acquired buoyancy to ascend into the surface waters, and then release the CH, thereby serving as a CH "pump" to the atmosphere. We tested this hypothesis using diel surveys and seasonal monitoring, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…While several studies have documented diurnal patterns in CH 4 ‐E (Deshmukh et al, 2014; Maher et al, 2019), the literature on diurnal patterns in CH 4 ‐D is somewhat mixed. For example, Carey et al (2017) failed to find a consistent diurnal pattern in CH 4 ‐D in a productive U.S. reservoir. Natchimuthu et al (2014) reported higher dissolved CH 4 concentrations during daylight hours in a small pond (average depth = 1.2 m), but it is not clear how patterns from a shallow pond would translate to patterns in our much larger reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have documented diurnal patterns in CH 4 ‐E (Deshmukh et al, 2014; Maher et al, 2019), the literature on diurnal patterns in CH 4 ‐D is somewhat mixed. For example, Carey et al (2017) failed to find a consistent diurnal pattern in CH 4 ‐D in a productive U.S. reservoir. Natchimuthu et al (2014) reported higher dissolved CH 4 concentrations during daylight hours in a small pond (average depth = 1.2 m), but it is not clear how patterns from a shallow pond would translate to patterns in our much larger reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…CCR and SHR are drinking water supply reservoirs for the city of Roanoke, Virginia, and have bubble plume oxygenation systems, which maintain oxic conditions in their hypolimnia throughout the year [36,37]. BVR, a secondary drinking water supply reservoir for the city of Roanoke, and GWR, a drinking water supply reservoir for the town of Pulaski, Virginia, USA, do not have oxygenation systems [37,38]. The hypolimnia of BVR and GWR become hypoxic after the onset of thermal stratification in the spring.…”
Section: Introductionmentioning
confidence: 99%
“…To reach the atmosphere, sediment‐produced CH 4 must be transported through the water column, where it can be consumed by methanotrophs (Rudd and Hamilton ; Utsumi et al ; Kankaala et al ; Bastviken et al ). Sediment‐produced CH 4 is transported in the water column by turbulent diffusion (Adams ), bubble‐mediated transport (McGinnis et al ), plant‐mediated transport (Juutinen ; Carmichael et al ), or migrating zooplankton (McGinnis et al ; Carey et al ). Although considerable efforts have been invested in quantifying the surface aquatic CH 4 fluxes and the relative contribution of the different emissions pathways (Bastviken et al ; Rinta et al ), the in‐lake mechanisms regulating rates of CH 4 production, transport, and oxidation in stratified systems are still poorly understood.…”
mentioning
confidence: 99%